Język litewski w Wielkim Księstwie Litewskim - Walczak, Bogdan (Scripta Neophilologica Posnaniensia, 2019)
The paper focuses on the Lithuanian language in the context of other Baltic languages. A brief history of Lithuanian in the Grand Dutchy of Lithuania is presented. It is done with reference to its oldest written records and the sociolinguistic underpinnings of the language. The national and linguistic revival of the Lituanians and the beginnings of scholarly interest in that language are briefly presented.